2014
DOI: 10.1057/ap.2014.22
|View full text |Cite
|
Sign up to set email alerts
|

Procedural fairness and political trust among young people: Evidence from a panel study on Swedish high school students

Abstract: The role of 'fair' institutions in developing democratic legitimacy has received increased attention. Citizens who perceive -on basis of past experiences -that they are being treated fairly by authorities have been held to have greater trust in political institutions. However, previous studies on the relationship between procedural fairness and political trust have not paid sufficient attention to individuals with limited first-hand experiences of authorities. We examine the relationship on an authority that v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 44 publications
2
21
0
Order By: Relevance
“…Therefore, we argue that individuals use evaluations of fair treatment by the police to form trust judgments for political institutions generally (see also Abdelzadeh et al. ; Van Sluis & Van de Walle ).…”
Section: Why Fair Treatment Perceptions Mattermentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we argue that individuals use evaluations of fair treatment by the police to form trust judgments for political institutions generally (see also Abdelzadeh et al. ; Van Sluis & Van de Walle ).…”
Section: Why Fair Treatment Perceptions Mattermentioning
confidence: 99%
“…Accordingly, street-level bureaucrats' 'behaviors function as important signals to citizens about the moral standard of the society in which they live' (Rothstein & Stolle 2008: 246). Therefore, we argue that individuals use evaluations of fair treatment by the police to form trust judgments for political institutions generally (see also Abdelzadeh et al 2015;Van Sluis & Van de Walle 2015).…”
Section: Why Fair Treatment Perceptions Mattermentioning
confidence: 99%
“…Fairness has consistently been emphasized in classroom assessment (CA) standards and practices as an essential quality and a significant dimension of teachers' assessment literacy (DeLuca, 2012;DeLuca, LaPointe-McEwan, & Luhanga, 2016;Xu & Brown, 2016). Empirical studies have demonstrated that teachers' fairness practices are associated with positive learning effects for students such as cognitive learning (Holmgren & Bolkan, 2014;Molinari, Speltini, & Passini, 2013), instructor satisfaction (Wendorf & Alexander, 2005), self-efficacy (Vallade, Martin, & Weber, 2014), legitimation of teacher and school authority (Gouveia-Pereira, Vala, Palmonari, & Rubini, 2003;Nelson, Shechter, & Ben-Ari, 2014), political trust (Abdelzadeh, Zetterberg, & Ekman, 2015), and positive evaluation of teacher expertise (Cronen & Fuller, 1976;Gotlieb, 2009;Rodabaugh & Kravitz, 1994). In contrast, perceived unfair behavior is associated with outcomes such as aggression and hostility (Horan, Chory, Carton, Miller, & Raposo, 2013;Uludag, 2014), truancy (Ishak & Fin, 2013), headache (Lenzi et al, 2013), and cheating (Lemons, Martin, & Seaton, 2011).…”
mentioning
confidence: 99%
“…The encounters people have with representatives of the state within public services can shape people's perceptions of legitimacy and representativeness (Peters, 2010). Moreover, how people evaluate public services can spill over into numerous other realms, such as institutional trust (Abdelzadeh, Zetterberg, & Ekman, 2015;Kumlin, 2009) or satisfaction with democracy (Ariely, 2013). Thus, interactions with public entities matter for people's willingness to participate in political life.…”
Section: Discussionmentioning
confidence: 99%